Bulb growth potential is independent of leaf longevity for the spring ephemeral Erythronium americanum Ker-Gawl. (29th October 2022) - Bertrand, Hugo; Lapointe, Line
Abstract: Growth in most spring ephemerals is decreased under warmer temperatures. Although photosynthetic activities are improved at warmer temperatures, leaves senesce earlier, which prevents the bulb from reaching a larger size. A longer leaf life duration during a warm spring, therefore, may improve bulb mass. We tested this hypothesis by modulating leaf life span of Erythronium americanum through the application of Promalin® (PRO; cytokinins and gibberellins) that prolonged or silver thiosulfate (STS) that reduced leaf duration. Gas exchange and chlorophyll fluorescence were measured along with leaf and bulb carbohydrate concentrations. Plants were also pulse labelled with 13 CO2 to monitor sugar transport to the bulb. Lower photosynthetic rates and shorter leaf life span of STS plants reduced the amount of carbon that they assimilated during the season, resulting in a smaller bulb compared with control plants. PRO plants maintained their photosynthetic rates for a longer period than control plants, yet final bulb biomass did not differ between them. We conclude that seasonal growth for E. americanum is not limited by leaf life duration under warm growing conditions, but rather by limited sink growth capacity. Under global warming, spring geophytes might be at risk of being reduced in size and, eventually, reproducing less frequently. Abstract : Warmer springs negatively affect trout lily growth, and delaying leaf senescence in this spring ephemeral does not translate into a larger bulb if temperatures remain high during springtime.